Human Development Index as a Predictor of Life Satisfaction - Ngoo, Yee Ting; Tey, Nai Peng (Institute for Population and Social Research, Mahidol University, 2019)
Since 1990, the Human Development Index (HDI) has been used by the United Nations to rank countries into four tiers of human development. Using data from the 2010 Human Development Report, this study has analyzed the mean life satisfaction of citizens from 144 countries that are at different levels of HDI. Simple regression analysis shows that HDI alone accounts for 63% of the variation in the mean life satisfaction across the countries. A strong positive correlation has been shown to exist between life satisfaction and HDI. However, countries with about the same level of HDI can have vastly different life satisfaction. Results from the Multiple Regression Analysis indicate that part of the variations in life satisfaction in countries with similar HDI is attributed to the personal dimensions of well-being-that being the percentage of the population that is satisfied with jobs, health, and standard of living, and to a lesser extent elements of happiness such as having a purposeful life and social support, and being treated with respect. In conclusion, while HDI is an important predictor of life satisfaction, there are many other socio-political and cultural factors as well, such as an individuals' traits and outlook in life throughout the world, also influence life satisfaction, to various degrees. © 2019 Journal of Population and Social Studies.